A Marine Carotenoid of Fucoxanthinol Accelerates the Growth of Human Pancreatic Cancer PANC-1 Cells. (2nd January 2022) - Terasaki, Masaru; Takahashi, Shouta; Nishimura, Ryuta; Kubota, Atsuhito; Kojima, Hiroyuki; Ohta, Tohru; Hamada, Junichi; Kuramitsu, Yasuhiro; Maeda, Hayato; Miyashita, Kazuo; Takahashi, Mami; Mutoh, Michihiro
Abstract: Fucoxanthin and its metabolite fucoxanthinol (FxOH), highly polar xanthophylls, exert strong anticancer effects against many cancer cell types. However, the effects of Fx and FxOH on pancreatic cancer, a high mortality cancer, remain unclear. We herein investigated whether FxOH induces apoptosis in human pancreatic cancer cells. FxOH (5.0 μmol/L) significantly promoted the growth of human pancreatic cancer PANC-1 cells, but induced apoptosis in human colorectal cancer DLD-1 cells. A microarray-based gene analysis revealed that the gene sets of cell cycle, adhesion, PI3K/AKT, MAPK, NRF2, adipogenesis, TGF-β, STAT, and Wnt signals in PANC-1 cells were markedly altered by FxOH. A western blot analysis showed that FxOH up-regulated the expression of integrin β1 and PPARγ as well as the activation of pFAK(Tyr 397 ), pPaxillin(Tyr 31 ), and pAKT(Ser 473 ) in PANC-1 cells, but exerted the opposite effects in DLD-1 cells. Moreover, the expression of FYN, a downstream target of integrin subunits, was up-regulated (7.4-fold by qPCR) in FxOH-treated PANC-1 cells. These results suggest that FxOH accelerates the growth of PANC-1 cells by up-regulating the expression of integrin β1, FAK, Paxillin, FYN, AKT, and PPARγ.